Human Rights Abuse and Policing in Nigeria: a case study of Niger State - Rabiu, Jamila (Direct Research Journal of Social Science and Educational Studies, 2024)
A survey method was utilized in this study to determine the effect of human right abuse and policing in Nigeria. A total population of 374,671 was used from the study area from which a sample of 540 respondents were selected using hat and draw method. A questionnaire was administered to the respondents by personal interview. The collected data was analyzed using appropriate statistical technique such as descriptive statistics and Pearson product moment correlation analysis. Test of significance was at 0.005 alpha level. The study reveals the causes of human rights violations by the Nigerian police force. The following suggestions were put forward by the researcher based on the findings of the study: There is the urgent need to improve the training of the Police in terms of human rights observance. The teaching of human rights education should be made compulsory at all levels of education in the country, most especially in Police Colleges and their Academies. Officers also need to be sensitized periodically over the rights of citizens and human rights issues generally. Better and improved conditions of service should be made for the police force. Welfare of the Police needs to be enhanced to minimize some of their excesses.